Aberrant splicing and defective mRNA production induced by somatic spliceosome mutations in myelodysplasia - Shiozawa, Yusuke; Malcovati, Luca; Gallì, Anna; Sato-Otsubo, Aiko; Kataoka, Keisuke; Sato, Yusuke; Watatani, Yosaku; Suzuki, Hiromichi; Yoshizato, Tetsuichi; Yoshida, Kenichi; Sanada, Masashi; Makishima, Hideki; et al. (Nature communications, 2018)
Spliceosome mutations are frequently found in myelodysplasia. Splicing alterations induced by these mutations, their precise targets, and the effect at the transcript level have not been fully elucidated. Here we report transcriptomic analyses of 265 bone marrow samples from myelodysplasia patients, followed by a validation using CRISPR/Cas9-mediated gene editing and an assessment of nonsense-mediated decay susceptibility. Small but widespread reduction of intron-retaining isoforms is the most frequent splicing alteration in SF3B1 -mutated samples. SF3B1 mutation is also associated with 3′ splice site alterations, leading to the most pronounced reduction of canonical transcripts. Target genes include tumor suppressors and genes of mitochondrial iron metabolism or heme biosynthesis. Alternative exon usage is predominant in SRSF2 - and U2AF1 -mutated samples. Usage of an EZH2 cryptic exon harboring a premature termination codon is increased in both SRSF2- and U2AF1 -mutated samples. Our study reveals a landscape of splicing alterations and precise targets of various spliceosome mutations. Mutations to the splicing machinery may have an important role in myelodysplasia. Here, the authors describe splicing factor gene mutations in myelodysplasia and report tumor suppressor, epigenetic, iron metabolism and heme biosynthesis genes as their targets.